(untitled) (INTERNATIONAL SEMINAR, 2024)
This qualitative study explores students’ perceptions of mind mapping as a tool for enhancing writing skills in English as a Foreign Language (EFL) classrooms. Through semi-structured interviews and focus group discussions with twenty intermediate EFL learners, the research investigates how mind mapping influences their writing processes, creativity, and overall engagement with the language. The findings reveal that students view mind mapping as a valuable strategy that aids in organizing their thoughts, generating ideas, and improving their confidence in writing. Participants also express a preference for visual learning tools, highlighting the role of mind mapping in making the writing process more enjoyable and less intimidating. This study contributes to the understanding of student-centered approaches in language education and emphasizes the importance of incorporating innovative strategies to foster effective writing skills